Core-shell structured CoP/FeP porous microcubes interconnected by reduced graphene oxide as high performance anodes for sodium ion batteries. (February 2017) - Li, Zhaoqiang; Zhang, Luyuan; Ge, Xiaoli; Li, Caixia; Dong, Shihua; Wang, Chengxiang; Yin, Longwei
Abstract: Confronted with the difficult in tuning the microstructures (components, crystalline state and particle size) of metal phosphide anodes for sodium ion batteries (SIBs), it is of great challenge and fundamentally important to develop a rational strategy to design hierarchically porous structure metal phosphide anodes for high-performance SIBs. Herein, for the first time, a unique core-shell porous FeP@CoP phosphide micocubes interconnected via reduced graphene oxide (RGO) nanosheets (RGO@CoP@FeP) are for the first time synthesized via a low-temperature phosphorization process using prussion blue as reactant template. The RGO@CoP@FeP hierarchical architecture SIBs anodes exhibit greatly improved reversible capacity, cycling stability and excellent rate capability. The enhanced electrochemical performance of RGO@CoP@FeP is ascribed to the uniquely porous core-shell microstructure and synergistic effect between the phosphide components. The core-shell structure with FeP as core and CoP as shell can provide enough cushion spaces for volume changes, as well as shorten the Na + diffusion path. The interconnected RGO nanosheets and carbon layer wrapped on the FeP core cubes together build a conductive highway, enhancing charge transfer kinetics. The present strategy using MOFs as reactant templates for porous core-shell phosphide electrodes can be extended to other novel electrodes for high performance energy storage devices. Graphical abstract: Highlights: Core-shell porous RGO@CoP@FeP are synthesized by using PB as template. The RGO@CoP@FeP anodes for SIBs exhibit greatly improved electrochemical performance. Using MOFs as templates for porous phosphides can be extended to other novel electrodes.